FRI0235 Adherence to the recommended dosing regimen of abatacept: results from the international, real-world action study. (23rd January 2014) - Nüßlein, H.; Alten, R.; Galeazzi, M.; Lorenz, H. M.; Boumpas, D.; Nurmohamed, M. T.; Bensen, W. G.; Burmester, G. R.; Peter, H.-H.; Rainer, F.; Pavelka, K.; Chartier, M.; et al.
Abstract : Background: In real-life, dosage increases are often described with biologic agents. 1 Intravenous (IV) abatacept should be administered by patient body weight (10 mg/kg) 2 and 4 weeks (wks) after the first infusion and every 4 wks thereafter, 2 totalling 8 infusions over the first 6 months (mths). No adjustments to this schedule are recommended. Abatacept retention rates, efficacy and safety over 12 mths in ACTION have been reported previously. 3, 4 Objectives: To assess adherence to the recommended dosing regimen of abatacept over the first 6 mths of treatment in ACTION. Methods: ACTION is an ongoing, 2-year, international, non-interventional, prospective cohort of RA patients treated with IV abatacept. All patients on abatacept treatment for ≥6 mths, and with infusion data available at initiation and at 6 mths, were considered in this analysis. Good adherence to treatment was defined as correct dose by patient body weight and number of actual-to-recommended infusions within the range 80–120% (i.e. 7–9 infusions). Results: 783/1120 (69.9%) patients received abatacept ≥6 mths and had infusion data available at initiation and 6 mths. The majority had established RA and failed ≥1 anti-TNF agent (87.5%). Of 774 patients with body weight data available at initiation, 87.6% received the recommended initial dose, 6.5% a lower dose and 5.9% a higher dose than recommended. Good adherence to the abatacept treatment schedule (7–9 infusions) was found in 670/783 (85.6%) patients. Over 6 mths, 34.0% of patients received 7 infusions, 50.1% received 8 infusions and 1.5% had 9 infusions. Change in dosage over time was assessed in 680/774 patients with data available at both initiation and 6 mths. The majority of patients (86.6%) maintained the recommended dosage over time. 500/680 (73.5%) patients received abatacept at the recommended dose for their weight (10 mg/kg) and at the recommended treatment schedule (7–9 infusions) over 6 mths. Conclusions: In the real-world ACTION study, adherence to the recommended treatment regimen of abatacept over 6 mths was good. Few patients received changes in dose and/or frequency of administration over this time period. References: Ariza-Ariza R, et al. Rheumatology 2007;46 :529-32; Abatacept EU SmPC; Nüßlein H, et al. Arthr Rheum 2012;64 (Suppl10):S199; Nüßlein H, et al. Ann Rheum Dis 2011;70 (Suppl.3):464 Disclosure of Interest : H. Nüßlein Consultant for: Bristol-Myers Squibb, Abbott, Chugai, UCB, Essex, Wyeth, Pfizer, MSD, Novartis, Roche, Speakers bureau: Bristol-Myers Squibb, Abbott, Chugai, UCB, Essex, Wyeth, Pfizer, MSD, Novartis, Roche, R. Alten Grant/research support from: Bristol-Myers Squibb, Merck Pharma GmbH, Wyeth Pharmaceuticals, Pfizer, Consultant for: Abbott Laboratories, Horizon Pharma, Merck Pharma GmbH, Nitec Pharma GmbH, Novartis Pharmaceuticals Corporation, Roche, Speakers bureau: Abbott Laboratories, Bristol-Myers Squibb, Horizon Pharma, Merck Pharma GmbH, Novartis Pharmaceuticals Corporation, Roche, M. Galeazzi: None Declared, H. Lorenz Speakers bureau: Bristol-Myers Squibb, D. Boumpas Grant/research support from: Unconditional educational grant support, M. Nurmohamed Grant/research support from: The Jan van Breemen Research Institute has received research grants from Bristol-Myers Squibb, MSD, Roche, Abbott, Pfizer, UCB, Consultant for: Bristol-Myers Squibb, MSD, Roche, Abbott, Pfizer, UCB, Employee of: Jan van Breemen Research Institute, VU University Medical Center, Speakers bureau: Bristol-Myers Squibb, MSD, Roche, Abbott, Pfizer, UCB, W. Bensen Grant/research support from: Abbott, Amgen, Bristol-Myers Squibb, Janssen, Merck, Lilly, Novartis, Pfizer, Proctor and Gamble, Roche, sanofi aventis, Schering, Takeda, UCB, Warner Chilcott, Wyeth, Consultant for: Abbott, Amgen, Bristol-Myers Squibb, Janssen, Merck, Lilly, Novartis, Pfizer, Proctor and Gamble, Roche, sanofi aventis, Schering, Takeda, UCB, Warner Chilcott, Wyeth, Speakers bureau: Abbott, Amgen, Bristol-Myers Squibb, Janssen, Merck, Lilly, Novartis, Pfizer, Proctor and Gamble, Roche, sanofi aventis, Schering, Takeda, UCB, Warner Chilcott, Wyeth, G. Burmester Grant/research support from: Bristol-Myers Squibb, Abbott, Pfizer, Medimmune, Novartis, Roche, UCB, Lilly, Consultant for: Bristol-Myers Squibb, Abbott, Pfizer, MSD, Medimmune, Roche, UCB, Speakers bureau: Bristol-Myers Squibb, Abbott, Pfizer, MSD, Roche, UCB, H.-H. Peter Speakers bureau: Pfizer Germany, F. Rainer: None Declared, K. Pavelka Consultant for: Roche, Abbott, MSD, Amgen, Speakers bureau: Pfizer, MSD, UCB, Bristol-Myers Squibb, M. Chartier Consultant for: Bristol-Myers Squibb, C. Poncet Consultant for: Bristol-Myers Squibb, C. Rauch Employee of: Bristol-Myers Squibb, M. Le Bars Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb